Case Study of the Vættaskóli-Engi Building: Life Cycle Cost and Thermal Analysis of an Alternative Building Enclosure System Design - Añover, Jose Wilon D., 1980- (2015)
This thesis presents a research study on existing building structure – Vættaskóli-Engi, an almost two decade old school structure. This research focused on the building enclosure system with the intention of stating alternative scenarios for choice of materials and technical design by utilizing a more cost-effective strategy through application of Life Cycle Cost Analysis. The building enclosure systems such as roofs and walls were investigated and compared by estimating the cost of ownership over a 60 year service life. A detailed estimation of labor cost, material cost and equipment cost of the building components was conducted based on the data from a successful building construction project. The building enclosures were designed according to the common construction practices in Iceland at the time of building in 1996 and the components used were readily available on the local market. The permitted maximum system U-values of Iceland Building Regulation was used as a boundary condition in the design. Thus, comprehensive calculations on thermal transmittance of the systems were performed. A thermal analysis was conducted using a simulation program WUFI modelling to calculate the energy consumption and energy demand for the whole building.